Ultrasonic examination of the tongue shape changes in the process of articulation of vowels - Gudra, Tadeusz; Opieliński, K.J.; Sobczak, T. (Archives of Acoustics, 2006)
This paper presents results of ultrasonic examination of changes in tongue shape during theprocess of articulation of vowels by people (without pronunciation disorders). The position ofthe tongue while pronouncing a definite vowel and the influence of individual anatomicaldifferences upon the tongue shape were examined. Results are presented as ultrasonogramsobtained in the B- and TM-type presentations. The TM mode enables, among others, determiningthe amplitude of deflection of a point on the tongue surface during articulation that isthe most change-prone at a given distance from the hyoid bone. Obtained results were used fordesign and construction of a tongue phantom and a mechanical setup to control the phantomshape. The proposed tongue phantom is crucial element of a natural tongue motions simulatorduring articulation that can be used as a major tool in therapy of deaf people, people withhearing and pronunciation disorders.